Administration of Disodium Cromoglycate for Ulcerative Colitis - Kurita, T.; Furukawa, T.; Hayashi, S.; Fukushima, T. (Nippon Daicho Komonbyo Gakkai Zasshi, 1989)
We carried out a study on the clinical effect of administration of disodium cromoglycate (DSCG), an anti-allergic agent, in cases of ulcerative colitis. The subjects were 19 patients diagnosed as having ulcerative colitis according to their clinical condition, progress, X-ray diagnosis and endoscopic findings. Details of the patients were : male female 12, aged between 13 years and 65 years at first visit, average age 28.3 years ; total colitis type 6, left-sided colitis type 9, proctitis type 4 ; serious cases 2, moderate cases 6, slight cases 11; treated with salazosulfapyridine 3, treated with steroid 1; hospitalization 5, outpatients 14 ; allergic malady in past or family histories 8. After prescribing DSCG 240-600mg orally per day depending on each symptom, we examined the effects according to the symptoms before and after medication, the findings of blood examinations and the endoscopic changes. After two months of DSCG administration, only one case was improved endoscopically, but the symptoms of ulcerative colitis disappeared satisfactorily in 12 cases out of 19. Based on the judgement of treatment effect by Dr. Tsuchiya and others, 14 cases out of 19 were found to be considerably effective and/or effective and only 5 examples were ineffective, Two of the five ineffective cases improved later. In other words, only two cases showed complete ineffectiveness of treatment, and DSCG showed an extremely high utility ratio. It was thus clearly indicated that immediate-type allergy is closely related to the onset of ulcerative colitis. We therefore hope that DSCG which controls the degranulation of mast cells will be widely used as a therapeutic medicine for ulcerative colitis.